2016
DOI: 10.1186/s40064-016-3436-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the performance management information system in improving performance: an empirical study in Shanghai Ninth People’s Hospital

Abstract: Improving the performance of clinical departments is not only the significant content of the healthcare system reform in China, but also the essential approach to better satisfying the Chinese growing demand for medical services. Performance management is vital and meaningful to public hospitals in China. Several studies are conducted in hospital internal performance management, but almost none of them consider the effects of informational tools. Therefore, we carried out an empirical study on effects of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The study, therefore, concluded that there is a significant relationship at α=0.05 that indicates a positive linear relationship between recruitment information systems and management of human capital. These findings were consistent with those of Asare, 2019;Mulegi, 2014;Arefin and Hosain, 2019;Cui, Wu, Lu, Jin, Dai, and Bai, 2016;Margatama, 2017).…”
Section: Inferential Statisticssupporting
confidence: 91%
“…The study, therefore, concluded that there is a significant relationship at α=0.05 that indicates a positive linear relationship between recruitment information systems and management of human capital. These findings were consistent with those of Asare, 2019;Mulegi, 2014;Arefin and Hosain, 2019;Cui, Wu, Lu, Jin, Dai, and Bai, 2016;Margatama, 2017).…”
Section: Inferential Statisticssupporting
confidence: 91%
“…5,19 However, during information system implementation, there may be positive impacts of leaders engaging in follow-up activities, such as assisting in the removal of barriers and taking a proactive approach during resistance, requesting updates, and providing feedback through performance data. 3,20 Studies related to information systems and managerial work have often focused on support for strategic planning and the scheduling of resources concluding deficiencies in interoperability and usability issues. [13][14]21 Competencies managers and leaders need to use health information technology have been less well studied.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, nurse managers' need for data to manage nursing services across levels is obvious, although the data sources in databases for decision-making may vary and be scattered or scarce. 3 However, a review of nursing management information systems found that they provided user satisfaction, timesaving, and usefulness for nurses. 4 In many countries, the use of electronic information systems is an integral part of daily nursing practice, and nurses may need to access a variety of systems to record patient data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximising hospitals’ service performance has been prioritised worldwide,9 and this has also influenced the primary content of the healthcare system reform in China 10. Before 2020, no province in China has implemented the DRG payment system in all public hospitals because this payment system is costly and requires advanced information systems.…”
Section: Introductionmentioning
confidence: 99%